Pore types in the Blue Nile shale from the Blue Nile Basin using FE-SEM Method: Contribution to understanding gas storage - Adam Shoieb, Monera; Weng Sum, Chow; Suhaili Ismail, Mohd; Tsegab, Haylay; Saleem, Tasneem (International Journal of Engineering and Technology, 2018)
Successful exploration and development of shale gas reservoirs have enabled the United States to ensure a predominantly domestic supply of gas for many years. Pore structures can significantly impact the mechanical and physical properties of the rock such as permeability, strength and durability. Understanding the microstructures of the rocks accurately and quantitatively is essential to petroleum engineering for evaluating and development of oil and gas, especially for the unconventional reserves with abundant interior nanoscale pores such as shale. The pore structure and morphology of twelve shale samples from the Blue Nile Formation in the Blue Nile Basin were carried out by apply-ing Field emission scanning electron microscopy (FESEM). FESEM is a widely used technique to examine pore structures in shale reser-voirs. The results of FESEM show that the Blue Nile shale samples have nanoscale pores which can be classified into four types: inter-particle pores, organic pores, intra-particle pores and micro-fractures. The common types are inter-particle pores between the clay particles and organic nano-pores. These pores are all large enough to store gas molecules.Â Â Â